STRATEGI BERSAING PRODUK UKM LUNPIA DENGAN MENGGUNAKAN ANALISIS FIVE FORCES PORTER DAN SWOT (Kasus pada UKM Lunpia Kings Semarang) - Annisa Novceria Rahma; Ari Pradhanawati (Universitas Diponegoro, 2018)
This study aims to determine the business strategy of SME (Small Medium Enterprise) Lunpia Kings business based on competitive position and business type by using Five Forces Porter Analysis and SWOT Analysis. The type of research used in this study is descriptive analytical. Determination of informants in this study using purposive sampling technique. The analytical technique used is to examine all data from various sources; data reduction; and SWOT analysis. Based on the results of tests conducted it can be concluded that based on the Five Forces Porter method business strategy that can be developed by SME Lunpia Kings is a cost leadership strategy, where SME Lunpia Kings are expected to reduce the production costs so as to reduce the selling prices. Based on the SWOT method, business development strategy SME Lunpia Kings is a market penetration strategy, whereby SME will penetrate the market to the middle economic community.